A study on the appoinment of councillors of local authorities in Malaysia / A.k Mohd Shaiful Nizam Pg. Mohd Noor, Muhammad Al-Hirzan Mahamad Akhir and Mohd 'Afif Ali - Pg. Mohd Noor, A.k Mohd Shaiful Nizam; Mahamad Akhir, Muhammad Al-Hirzan; Ali, Mohd 'Afif (2008)
This study concerns about the appointment of councillors in local authorities in Malaysia. Councillors consist of city mayor or council president and councillors, which are appointed by state authorities. Councillors are considered as people who represent the public in local authorities. Before the system of appointment of councillors take place, councillors were elected through the election of local government. However a change in the political landscape has resulted in the suspension of the electoral system until today. This resulted instead in the appointment of councillors, in which the system has caused several problems namely non-accountability, corruption, lack of transprerancy, nepotism, cronysym, and abuse of powers. These problems arise because of the interference by federal and state government and political parties even though the power of councillors is vested to the state government. This study would emphasize on the restoration of local government election with referance to the current need of the public. In addition to the reintroducition of the electoral system, other solutions would also be taken into consideration in order to address the weaknessess of the appoinment system of councillors in local authorities.